TYPOLOGY OF DIGITAL TECHNOLOGIES OF INCLUSIVE EDUCATIONAL SPACE - Semenikhina , Olena; Drushlyak, Marina (Physical and Mathematical Education, 2022)
Formulation of the problem. he need to provide access to quality education for people with special educational needs has led to public demand for the preparation of teachers who can operate in an inclusive environment effectively. At the same time, the active spread of digital technologies has highlighted the need to rethink learning environments, tools, and teaching means that involve all students in the educational process: such digital tools should be seen as tools for socialization and adaptation skills of every child in society. Materials and methods. To solve this problem, several theoretical methods of scientific research were used – the analysis of Internet sources, and analysis of digital tools of specialized direction to characterize those digital technologies and tools that will be appropriate for teachers in an inclusive educational space. Results. Digital technologies that are potentially useful for teachers in an inclusive educational space are characterized. The combined classification of digital technologies of inclusive direction is given. Software and hardware in three main directions (for training and repetition; to help with learning; to expand learning opportunities) are offered. Conclusions. Analysis of the state of development of the problem of professional training of pre-service bachelors of education in the use of digital technologies in an inclusive educational space showed that today introduced and implemented multi-vector scientific and pedagogical research related to inclusive education. The peculiarities of the introduction of digital technologies for the socialization of children with special educational needs, methodological support of their education in educational institutions of various types update scientific research on the use of mobile and remote technologies in the education of such children, and more. Also, the generalization of scientific results showed the systematic nature of the work on the specifics of working with children who need a special approach to learn for their further socialization in society, and fragmentary research on the preparation of bachelors of education to use digital technologies in an inclusive educational space.